Employment outcomes in people with bipolar disorder: a systematic review. (4th February 2013) - Marwaha, S.; Durrani, A.; Singh, S.
<x xml:space="preserve">Abstract</x> Objective Employment outcome in bipolar disorder is an under investigated, but important area. The aim of this study was to identify the long‐term employment outcomes of people with bipolar disorder. Method A systematic review using the Medline, PsychInfo and Web of Science databases. Results Of 1962 abstracts retrieved, 151 full text papers were read. Data were extracted from 25 papers representing a sample of 4892 people with bipolar disorder and a mean length of follow‐up of 4.9 years. Seventeen studies had follow‐up periods of up to 4 years and eight follow‐up of 5–15 years. Most studies with samples of people with established bipolar disorder suggest approximately 40–60% of people are in employment. Studies using work functioning measures mirrored this result. Bipolar disorder appears to lead to workplace underperformance and 40–50% of people may suffer a slide in their occupational status over time. Employment levels in early bipolar disorder were higher than in more established illness. Conclusion Bipolar disorder damages employment outcome in the longer term, but up to 60% of people may be in employment. Whilst further studies are necessary, the current evidence provides support for extending the early intervention paradigm to bipolar disorder.